2022
DOI: 10.3390/f13122176
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nutrient Transfer via Above- and Below-Ground Litter in Forests

Abstract: Plants periodically shed more than 90% of their biomass production as above- and below-ground litter, including leaves, twigs, flowers, logs, roots and other tissues [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In areas affected by landslides, soil organic carbon was likely the major limiting factor for soil formation and biological processes, as indicated by the significant decrease in soil organic carbon content (Dialynas et al, 2016). Moreover, K, Ca and Mg are macronutrient elements that play crucial roles in plant nutrient uptake and ecosystem functions, such as maintaining organism osmosis balance, improving water use efficiency, and decreasing water loss (Sardans and Penuelas, 2015;Tang et al, 2019;Hu and Lan, 2020;Wu et al, 2022). Our results revealed that the lower contents of AK, eCa, and eMg in areas affected by landslides than in unaffected areas suggested that earthquake-induced landslides might have influenced water balance in the plant-soil system.…”
Section: Earthquake-induced Landslides Affect Soil Nutrient Content A...mentioning
confidence: 99%
“…In areas affected by landslides, soil organic carbon was likely the major limiting factor for soil formation and biological processes, as indicated by the significant decrease in soil organic carbon content (Dialynas et al, 2016). Moreover, K, Ca and Mg are macronutrient elements that play crucial roles in plant nutrient uptake and ecosystem functions, such as maintaining organism osmosis balance, improving water use efficiency, and decreasing water loss (Sardans and Penuelas, 2015;Tang et al, 2019;Hu and Lan, 2020;Wu et al, 2022). Our results revealed that the lower contents of AK, eCa, and eMg in areas affected by landslides than in unaffected areas suggested that earthquake-induced landslides might have influenced water balance in the plant-soil system.…”
Section: Earthquake-induced Landslides Affect Soil Nutrient Content A...mentioning
confidence: 99%
“…Previous studies of forest litterfall C storage have primarily focused on mechanistic explanations of the impacts of litterfall on soil organic C solidification [18,19] and on the transfer of nutrients such as nitrogen and phosphorus [20,21]. There are significant correlations between litterfall types, microbial efficiency, and soil organic carbon (SOC) [22].…”
Section: Introductionmentioning
confidence: 99%